The Ameliorative Effects of Allium porrum (wild Leek) Against Cisplatin- Induced Nephrotoxicity in the Rabbit - Mohamed Ahmida; hajer Mohammed; Mohamed Mathi; Abdel-Gayoum (College of Pharmacy University of Baghdad, 2021)
Activities during dispensing process is vital in reducing antihypertensive and analgesics waste. However, study looking into refusal to accept cardiovascular disorders (CVD) medicines or analgesics activities during dispensing process is lacking. To determine differences in factors and costs associated with refused CVD medicines or analgesics during dispensing process This study was approved by Medical Research and Ethics Committee (MREC) (Registration number: NMRR-20-177-53153(IIR)). Participants receiving CVD medicines or analgesics during dispensing process were recruited via convenience sampling technique between February and March 2020 at the Outpatient Pharmacy Department of Jerantut Hospital, Malaysia. Refusal to medications and its reasons were asked based on the questionnaire developed by the researchers. Overall, 175 patients participated in this survey and CVD drugs contributed toward 58.9% of the refused medicines. Those who refused CVD drugs and analgesics were significantly different in terms of gender, medications dosing frequency, refusal reasons namely side effects, medications use, intentionally skipping dose and skipping the dose when feeling well. No associations were found between forgetfulness and age with refusal to CVD drugs or analgesics. Those who refused CVD medicines had a significantly higher total daily medicines, total daily pill burden, and total number of medicines refused per prescription compared to those who refused analgesics. Cost of CVD medicines refused per prescription was significantly higher compared to analgesics, median United States Dollar (USD) 2.58 (IQR, USD 3.69) versus median USD 1.47 (IQR, USD 3.69), P=0.01. Refusal to CVD medicines and analgesics was associated with several medication's and patient's factors. However, higher cost of refused medication was observed for CVD medicines.